2010
DOI: 10.1007/s10643-010-0427-8
|View full text |Cite
|
Sign up to set email alerts
|

Kindergarten Transition Preparation: A Comparison of Teacher and Parent Practices for Children with Autism and Other Developmental Disabilities

Abstract: The transition to kindergarten represents an important developmental milestone for children and may pose unique challenges to children with disabilities, their families, and teachers. The primary goal of the current study was to investigate teacher concerns regarding the transition to kindergarten as well as teacher and parent-reported transition preparation practices and involvement for a sample of children with autism spectrum disorders (n = 19) and children with other developmental disabilities (n = 76). Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 21 publications
1
53
0
8
Order By: Relevance
“…Starting school represents a major event which brings new demands and challenges for children with ASD and their families (Parsons, Lewis, & Ellins, 2009;Quintero & McIntyre, 2011;Weiss & Pearson, 2012). From a series of interviews with mothers of children with ASD in Australia, Lilley (2012Lilley ( , 2014 reported that parents experienced stigma and efforts by school professionals to exclude their children because of the ASD diagnosis.…”
Section: Literature On Parents' Experiences Of Their Children With Asmentioning
confidence: 99%
“…Starting school represents a major event which brings new demands and challenges for children with ASD and their families (Parsons, Lewis, & Ellins, 2009;Quintero & McIntyre, 2011;Weiss & Pearson, 2012). From a series of interviews with mothers of children with ASD in Australia, Lilley (2012Lilley ( , 2014 reported that parents experienced stigma and efforts by school professionals to exclude their children because of the ASD diagnosis.…”
Section: Literature On Parents' Experiences Of Their Children With Asmentioning
confidence: 99%
“…This case is analogous with the current research results. Some of the transition research related to teachers' characteristic also show that participants are generally female (Ahtola et al, 2011;Barblett, Barratt-Paugh, Kilgallon, & Maloney, 2011;Jewett et al, 1998;La Paro, Pianta, & Cox, 2000;Lo CasaleCrouch, Mashburn, Downer, & Pianta, 2008;Quintero & McIntyre, 2011). The current research includes mostly female teachers.…”
Section: Discussionmentioning
confidence: 68%
“…When cooperation exists between the special education teacher and general education teachers, general education can display positive effects on inclusion (Flores, 2012;Hwang & Evans, 2011). One defined problem in transitioning is the absence of cooperation and communication about transitioning in the body of literature (Barblett et al, 2011;Janus, Lefort, Cameron, & Kopenhanski, 2007;Jewett et al, 1998;Quintero & McIntyre, 2011;Wischnowski, Fowler, & McCollum, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disponível em: <https://periodicos.ufsm.br/educacaoespecial> Benefícios da intervenção precoce para a família de crianças com transtorno do espectro do autismo mais e informais, os quais aumentam o sentimento de controle sob os serviços da IP (CRUZ; FONTES; CARVALHO, 2003;DEMPSEY;KEEN, 2008;QUINTERO;MCINTYRE, 2010;STONER, et al, 2007).…”
Section: Santa Mariaunclassified